ANTAGONIST TEST OF TRICHODERMA HARZIANUM AGAINST GANODERMA BONINENSE CAUSES OF OIL PALM BASAL STEM ROT DISEASE - Kusmawanto, Arif; Himawan, Achmad; Kristalisasi, Elizabeth Nanik (ITScience (Information Technology and Science), 2022)
This study aims to determine the type of Trichoderma fungus that can inhibit the growth of G. boninense and determine the percentage of inhibition of Trichoderma on the growth and development of G. boninense. This research was conducted at the Central Laboratory of the STIPER Agricultural Institute Yogyakarta in February-March 2022. G. boninense samples were taken from three different plantation locations belonging to residents of Aek Paing Atas Village and Aek Paing Bawah Satu Village, Kec. Rantau Utara, Kab. Labuhan Batu and Aek Janji Village, Kec. Rantau Selatan, Kab. Labuhan Batu, North Sumatra. Trichoderma samples were taken from Naga Soppah Village, Naga Harjo Village and Bahung Kahean Village. The research method used is descriptive by identifying antagonistic (Trichoderma) and pathogenic (G. boninense) fungi. Data on the percentage of inhibition of fungi were analyzed quantitatively. Fungi macroscopic and microscopic characterizations were analyzed qualitatively. The results showed that the Trichoderma fungus that could inhibit the growth of G. boninense was T. harzianum. The highest percentage of inhibition power of T. harzianum (Naga Soppah Village) against G. boninense (Aek Paing Bawah Satu village) was 30%.